Current Social Studies Learning: Technology-Based Learning Media for Character Education - Salamah, Umi; Naysilla, Nawang; Juliadi, Ertawan (CV. Edutechnium Indonesia, 2024)
This study investigates the integration of technology-based learning media in social studies education, focusing on its influence on character education. The primary aim is to explore how digital tools and platforms can enhance the teaching and learning process, promoting values such as responsibility, empathy, and civic engagement among students. Utilizing a mixed-method approach, the research combines qualitative interviews and quantitative surveys to assess the effectiveness of technology in character education. The study includes 500 middle and high school students from diverse geographical locations, selected based on their schools' adoption of technology in the social studies curriculum. Preliminary findings suggest that the integration of technology significantly improves student engagement and the internalization of character values. However, challenges such as the digital divide, which can exacerbate educational inequalities, and the need for comprehensive teacher training to effectively use these tools, were identified. To mitigate these issues, the study recommends implementing policies to ensure equitable access to technology and developing robust professional development programs for educators. In conclusion, while digital tools have the potential to revolutionize character education in social studies, addressing the identified challenges is crucial for maximizing their benefits. The research underscores the necessity for a more inclusive approach to technology access and enhanced teacher training to fully realize the advantages of technology-based learning media.